p-Laplacian Equations in R + N with Critical Boundary Nonlinearity - Xu Miao; Junfang Zhao; Xiangqing Liu (Mathematics, 2020)
In this paper, we consider the following p-Laplacian equation in <semantics><msubsup>R+N</msubsup></semantics> with critical boundary nonlinearity. The existence of infinitely many solutions of the equation is proved via the truncation method.